2008
DOI: 10.1186/1743-7075-5-36
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a low-carbohydrate, ketogenic diet versus a low-glycemic index diet on glycemic control in type 2 diabetes mellitus

Abstract: Objective: Dietary carbohydrate is the major determinant of postprandial glucose levels, and several clinical studies have shown that low-carbohydrate diets improve glycemic control. In this study, we tested the hypothesis that a diet lower in carbohydrate would lead to greater improvement in glycemic control over a 24-week period in patients with obesity and type 2 diabetes mellitus.Research design and methods: Eighty-four community volunteers with obesity and type 2 diabetes were randomized to either a low-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
405
11
45

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(504 citation statements)
references
References 26 publications
22
405
11
45
Order By: Relevance
“…Two recent modest-sized randomized trials found that lowcarbohydrate high-protein consumption over 6-12 months had no effect on serum creatinine compared with low-fat or low-glycemic diets, but no other markers of GFR, such as cystatin C and urinary creatinine clearance, were measured (13,53). In an observational study of 39 participants (54), a low-carbohydrate high-protein weight loss diet had no clinically significant effects on acid-base or electrolyte status, similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent modest-sized randomized trials found that lowcarbohydrate high-protein consumption over 6-12 months had no effect on serum creatinine compared with low-fat or low-glycemic diets, but no other markers of GFR, such as cystatin C and urinary creatinine clearance, were measured (13,53). In an observational study of 39 participants (54), a low-carbohydrate high-protein weight loss diet had no clinically significant effects on acid-base or electrolyte status, similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, a few studies, such as [6][7][8], investigated diet as a possible adjuvant to cancer treatment, which includes a ketogenic diet. A ketogenic diet consists of high edible fat with moderate or low protein content and very low carbohydrates, which forces the body to burn fat instead of glucose for adenosine triphosphate (ATP) synthesis [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, strategies (1-3) use the objective functional (8). We assumed that there are practical limitations on the maximum rate at which the anti-cancer treatment may be applied in a given time period.…”
mentioning
confidence: 99%
“…El producto de glicación más común es la hemoglobina A1c (HbA1c) que es ampliamente utilizada como control metabólico y en algunos casos como diagnóstico (9). Es universalmente aceptado que la ingesta de CHO es la principal determinante de la glicemia (10) y que la restricción de CHO especialmente los de absorción rápida, muestra una mayor reducción en los niveles de glucosa postprandial y HbA1c (11)(12)(13).…”
Section: Introductionunclassified